A Case of Osteomyelitis after Calcaneal Fracture Treated by Antibiotic-Containing Calcium Phosphate Cements - Yoohak Kim; Fumiaki Inori; Kiyotaka Yamanaka; Shouichi Murakami; Eri Narita; Kazumasa Yamamura; Hiroyuki Yasuda; Makoto Fukuda; Sadahiko Konishi; Yukihide Minoda (Case Reports in Orthopedics)
Calcaneal osteomyelitis (CO) is considered to be difficult to cure when it turned into a chronic phase. We report one case of calcaneal osteomyelitis which arises after the operation of calcaneal fracture. Remission was obtained by performing curettage of the infected cancellous bone of the calcaneal body and filling antibiotic-containing calcium phosphate cements (CPC) within its bone defect. This one-stage surgery is useful to treat calcaneal osteomyelitis.